1998
DOI: 10.1063/1.367830
|View full text |Cite
|
Sign up to set email alerts
|

Unusual properties of the molecular nanomagnet Mn12ac

Abstract: Articles you may be interested inSlow magnetic relaxation and electron delocalization in an S = 9/2 iron(II/III) complex with two crystallographically inequivalent iron sites Resonant magnetic quantum tunneling through thermally activated states Thermally assisted macroscopic quantum resonance on a single-crystal of Mn 12 -acetateThe magnetic properties of the Mn 12 ac molecular cluster were studied by complex susceptibility and specific heat measurements. Extensive ac susceptibility measurements done under a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…(1) as a function of temperature at 0.45 T are compared in Fig. 2 with the results obtained in Mn12 from magnetization [6] and specific heat [27] measurements. The NMR set of data shows little scatter and is in good agreement with the measurements obtained at approximately the same field H with the SQUID, confirming that we have a new microscopic method to study the relaxation of magnetization in molecular clusters.…”
Section: (Received 28 September 1999)mentioning
confidence: 96%
“…(1) as a function of temperature at 0.45 T are compared in Fig. 2 with the results obtained in Mn12 from magnetization [6] and specific heat [27] measurements. The NMR set of data shows little scatter and is in good agreement with the measurements obtained at approximately the same field H with the SQUID, confirming that we have a new microscopic method to study the relaxation of magnetization in molecular clusters.…”
Section: (Received 28 September 1999)mentioning
confidence: 96%
“…The temperature dependence of heat capacity of several Mn12 compounds was reported for polycrystalline samples and for single crystals. In several works, clear heat-capacity drops at T B were observed by application of magnetic field. ,, Because the dipolar fields exerted from neighboring molecules are also effective to remove the degeneracy of the ground doublet, the heat capacity under zero external field was closely examined to obtain the information on the freezing process . The results showed lowering of the T B and the blocking process over a certain temperature range.…”
Section: 1 Dodecanuclear Manganese Clusters (Mn12)mentioning
confidence: 99%
“…Similar thermal anomalies were also found in Mn 12 Ac. 18,23 We shall discuss the origin of these thermal anomalies later.…”
Section: Resultsmentioning
confidence: 99%
“…The heat capacity due to the hyperfine interaction of the Mn nuclei C hf was actually observed in Mn 12 -Ac. 18,23 In the case of Mn 12 Pr, C hf is remarkably below 0.5 K. In the analysis of the results below 5 K in a zero magnetic field using eq 3, it was revealed that two kinds of spin clusters characterized by different D values should be incorporated into the model. This just corresponds to the Jahn-Teller isomers mentioned previously.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation